Evidence Focused Social Care: on Target or Off-Side? - Ian Dore (Social Work and Society)
As contentions continue to engulf the evidence-based practice (EBP) debate within social care, consensus seems to be gravitating towards the softer term of "˜evidence-aware' practice, although there is as yet no definitive concept on the horizon. Set against a back-drop of competing ideologies, heavily influenced by the natural sciences, what is at stake is the essence of social work: there is a real danger that social work practice be reduced to mere base elements, which seek to eliminate all notions of uncertainly, so essential and endemic to our social world; a characteristic of our very being. Underlying the surface arguments that an evidence-focused approach can realise better practice, are questions of power and control. In exploring the current position of EBP within UK social care, this paper argues that as an interpersonal profession, operating within the complexities of the social world, social work would be better suited to pursue an inclusive "˜knowledge-aware' approach to practice, which may allow the profession to move beyond the restrictive and limiting polemics that surround it. Deliverance of a deserving future will require a brave and frank acceptance of our own fallibility, together with an openness which allows the profession to harness its key values.